Position-related differences in cardiorespiratory functional capacity of elite basketball players - Gocentas, A.; Jascaniniene, N.; Poprzecki ,S.; Jaszczanin, J.; Juozulynas, A. (Journal of Human Kinetics, 2011)
The purpose of this study was to examine possible differences in cardio respiratory functional capacity between perimeter and post elite basketball players. The subjects included 42 highly trained basketball players subdivided into groups of perimeter and post players. Point guards, shooting guards and small forwards were involved in the group of perimeter players, while power forwards and centers represented the group of post players. All players performed a standardized exercise test to evaluate maximal oxygen uptake using a cycle ergometer and automated breath-by-breath system VMAX229C. Collected data of power, heart rate, pulmonary ventilation and gas exchange were compared between the groups of perimeter and post players. Significant differences in anthropometric features between the investigated subgroups were observed. Post players were heavier and taller. Therefore, the perimeter players had significantly higher values of VO2max and relative power. VO2max was related to relative power. Relations between those variables can be described by linear regression. Given regressions can be used as a source of typical values for male basketball players. The results indicate that the empirical repartition of basketball players into perimeter and post players has not only a morphological but a physiological basis as well.